Management of Depression in Children With Lupus Erythematosus System - Risza Subiantoro; Sasanti Yuniar; Endang Warsiki; Lestari Basoeki Soeharjono (Faculty of Medicine, Universitas Airlangga, 2021)
ABSTRACT Depression is a comorbid in patients with Systemic Lupus Erythematus (SLE). Depression can affect up to 60% of adolescents who are comorbid. Depression in adolescents is likely many factors, etiology, psychological burden, chronic disease, effects of long term steroid treatment, social, cultural and genetic factors. Depression is frequently associated with poorer treatment outcomes and poor treatment and health care outcomes in individuals with SLE. In this case, we will discuss the available treatment options. Keyword: Child Depression, Erythematous Systemic Lupus, Management.